The Mediating Effect of Job Satisfaction and Burnout Between Job Stress and Organizational Commitment In the Saudi Private Sector - Nassani, Abdelmohsen; Alwuhebi, Jumana; Alzeer, Latifa (The Arab Journal of Administration, 2023)
This study aims to measure the mediating effect of job satisfaction and burnout between job stress and organizational. A questionnaire of 27 items was distributed among private sector workers in Saudi Arabia, and 244 were collected for the purpose of this study. We hypothesized that job stress directly and positively is associated with burnout and negatively linked to job satisfaction. We also made a hypothesis that Job Stress could have an indirect effect on organizational commitment through job satisfaction. Besides this, job Satisfaction could also moderate the effect between burnout and organizational commitment. Additionally, job satisfaction is positively associated with organizational commitment. On the other hand, burnout could be a mediating factor between job stress and job satisfaction. There also could be a negative and direct relationship between burnout and job satisfaction. As expected, all our hypotheses were corroborated.